2015
DOI: 10.1586/14779072.2015.1074861
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the pathogenesis of abdominal aortic aneurysms

Abstract: Summary An aortic aneurysm is a dilatation in which the aortic diameter is ≥ 3.0 cm. If left untreated, the aortic wall continues to weaken and becomes unable to withstand the forces of the luminal blood pressure resulting in progressive dilatation and rupture, a catastrophic event associated with a mortality of 50 – 80%. Smoking and positive family history are important risk factors for the development of abdominal aortic aneurysms (AAA). Several genetic risk factors have also been identified. On the histolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
254
0
22

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(280 citation statements)
references
References 109 publications
4
254
0
22
Order By: Relevance
“…Based on these observations, we concluded that VPO1 modulates VSMC phenotypic switch through H 2 O 2 /VPO1/HOCl/ERK1/2 signaling pathway, which plays a key role in the formation of AAA. Oxidative stress has been described as an important signaling pathway in human AAA development and animal models of AAA 21, 22. The specific identity of reactive oxygen species that is responsible for the development of aortic dilation remains elusive 4, 23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these observations, we concluded that VPO1 modulates VSMC phenotypic switch through H 2 O 2 /VPO1/HOCl/ERK1/2 signaling pathway, which plays a key role in the formation of AAA. Oxidative stress has been described as an important signaling pathway in human AAA development and animal models of AAA 21, 22. The specific identity of reactive oxygen species that is responsible for the development of aortic dilation remains elusive 4, 23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…The natural course of an abdominal aortic aneurysm (AAA) is a steady increase of the diameter, and eventually, if left untreated, the aneurysm might rupture 1. In most cases of AAA, this pathophysiological process remains asymptomatic until rupture.…”
Section: Introductionmentioning
confidence: 99%
“…La capa media de la aorta torácica cuenta con alrededor de 60 unidades divididas en regiones vasculares y avasculares, mientras que la abdominal es completamente avascular y cuenta con alrededor de 30 unidades. Debido a las diferencias estructurales en los aneurismas torácicos y aórticos, generalmente no se presentan de manera concomitante, con solo un 10-15% de probabilidad de que un individuo presente enfermedad aneurismática en ambas porciones de la aorta 21 . Sin embargo, cabe señalar que en este estudio encontramos patología concomitante aislada en nueve pacientes y aneurismas con extensión toracoabdominal en 22 individuos.…”
Section: Figura 5 Gráfico De Regresión Lineal De La Población Estudiunclassified